Genetic and morphological diversity in Chara vulgaris L. (Characeae) - Noedoost, Fariba; Sheidai, Masoud; Riahi, Hossein; Ahmadi, Akram (Acta Biologica Szegediensis, 2015)
Chara vulgaris L. (Characeae) is a highly polymorphic species that plays an important ecological role in aquatic ecosystems. It grows in different regions of Iran and forms several geographical populations. Genetic diversity studies are very limited in algal taxa of the country and there is no detailed information about the genetic diversity present in C. vulgaris. Therefore, the present investigation was performed to study the population structure of 89 plant specimen collected from 11 geographical populations of C. vulgaris in Iran. Genetic diversity parameters were determined in each population based on ISSR molecular markers. AMOVA test revealed significant genetic difference among the studied populations. Mantel test revealed significant correlation between genetic distance and geographical distance of the studied populations. However, STRUCTURE analysis revealed that some common ancestral alleles exist among these populations. ANOVA test revealed significant differences in quantitative morphological characters among the studied populations. UPGMA tree and PCoA plot revealed morphological variability of these populations as the members of each population were scattered in different groups. Therefore, in spite of genetic differences of the studied populations, they are not morphologically differentiated.